A Systematic Literature Review on the CIPP Evaluation Model in Education: Examining Its Trends, Applications, and Research Gaps - Mentari Putri Wulan; Winda Dewi Listyasari; Heru Santosa; Syafa’At Ariful Huda (Journal of Educational Sciences, 2026)
This study aims to analyze the development, trends, applications, and research gaps of the CIPP (Context, Input, Process, Product) Evaluation Model in the field of education over the past decade (2015–2025). This review employs a Systematic Literature Review (SLR) approach guided by PRISMA 2020, based on a structured search in the Scopus database using Boolean codes. The selection process followed the four PRISMA stages: identification, screening, eligibility, and inclusion, resulting in 22 relevant articles for in-depth analysis. The findings indicate that the CIPP model remains a dominant and adaptable evaluation framework across diverse educational contexts, ranging from primary and secondary education to higher education and professional training. The thematic analysis reveals a methodological shift toward mixed methods, expert-based evaluation techniques (such as Delphi and AHP), as well as data-driven and technology-enhanced approaches. The Context and Input components demonstrate the highest performance, whereas the Process and Product components still require improvement. Despite its wide application, research gaps persist, particularly in longitudinal evaluation, digital-based assessment, and theoretical integration. This study offers a theoretical contribution by updating the state of the art of the CIPP model and provides practical insights for policymakers and educators to strengthen evidence-based and outcome-oriented educational evaluation practices.